Pengaruh Pekerja Keluarga dan Peran Inovasi terhadap Produktivitas Usaha di Indonesia - Lubis, Subhan Fikri; Lubis, Andi Fahmi (Jurnal Ekonomi dan Pembangunan Indonesia, 2020)
The purpose of this study is to estimate the influence of family involvement through business ownership (own capital) and the involvement of family members (family workers) in companies/micro and small enterprises in Indonesia on the productivity of their business. Based on previous studies, family involvement can decrease and increase productivity. With relatively small capital, less qualified workforce and low technology productivity of micro and small industries that employ family members within the company will tend to be lower because they will be more avoiding risky changes. The role of innovation can be proven as moderate in the research is expected to improve the productivity of micro and small industries in Indonesia.